Occupational exposure to nanomaterials and biomarkers in exhaled air and urine: Insights from the NanoExplore international cohort - Maud Hemmendinger; Giulia Squillacioti; Thomas Charreau; Giacomo Garzaro; Federica Ghelli; Roberto Bono; Jean-Jacques Sauvain; Guillaume Suarez; Nancy B. Hopf; Pascal Wild; Athena Progiou; Carlos Fito; et al. (Environment International, 2023)
The current evidence on nanomaterial toxicity is mostly derived from experimental studies making it challenging to translate it into human health risks. We established an international cohort (N = 141 workers) within the EU-LIFE project “NanoExplore” to address possible health effects from occupational exposures to nanomaterials. We used a handheld direct-reading optical particle counter to measure airborne nanoparticle number concentrations (PNC) and lung-deposited surface areas (LDSAs). Airborne particles were characterized by TEM and SEM-EDAX. We assessed oxidative/nitrosative stress with a panel of biomarkers in exhaled breath condensate (EBC) (8-isoprostane, malondialdehyde, nitrotyrosine), inflammation (high-sensitivity C reactive protein (hs-CRP), IL-1β, TNF-α, IL-10) and KL-6 (considered as biomarker of interstitial lung fibrosis) and urine (total antioxidant power (TAP), 8-isoprostane, and malondialdehyde). Exhaled breath sampled in gas-sampling bags were assessed for oxidative potential. These biomarkers were quantified pre-shift at the beginning of the workweek and post-shift the 4th day. Relationships between airborne nanoparticle concentration and biomarkers were assessed by multiple linear regression with log-transformed exposure and biomarker concentrations adjusted for potential confounders. We found a positive dose–response relationship for three inflammation biomarkers (IL-10, IL-1β and TNF-α) in EBC with both PNC and LDSA. A negative dose–response relationship was observed between PNC and TAP. This study suggests that occupational exposures to nanoparticles can affect the oxidative balance and the innate immunity in occupationally exposed workers. However, owing to the intrinsic variability of biomarkers, the observed changes along with their health significance should be assessed in a long-term perspective study.